Spine Surgery Basics - Patel, Vikas V.; Patel, Alpesh; Harrop, James S.; Burger, Evalina (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Spine surgery has increasingly become a surgical field of its own, with a distinct body of knowledge. While available textbooks cover the intricacies of spine surgery and provide extensive information on each pathology, these books are not geared towards the requirements of the novice and are insufficiently portable for the busy resident to carry while on rounds or on call.   This easy-to-use book, written by acknowledged experts, is designed to meet such needs by providing essential information on spine pathology, diagnostic evaluation, surgical procedures, and other treatments. After an opening general section, degenerative spinal disease, pediatric spine conditions, spine trauma, spine tumors, infections, inflammatory disorders, and metabolic conditions are all discussed in more depth. Alongside description and evaluation of surgical options, important background information is included on pathology, presentation, diagnosis, and nonsurgical treatments. Potential complications of surgery are also carefully considered. Spine Surgery Basics will be an invaluable practical aid for all who are embarking on a career in spinal surgery or require a ready reference that can be consulted during everyday clinical practice.